ДӨРВӨЛЖИН ҮСГЭЭР ҮЛДЭЖ ИРСЭН ХУБИЛАЙ ХААНЫ ГЭРЭЭС - Ш.Баатар (Acta Mongolica, 2010)
Shirchin Baatar, a visiting scholar in the Khitan studies at the Institute of East Asian Studies at University of California Berkeley. In the making of the “Khubilai Khan and Mongolian Empire” documentary, the NHK Special program coordinating group rediscovered Khubilai Khan’s last wishes, all written on a single page of a Yuan history book that is archived at the Topkapi Palace Museum Library in Istanbul, Turkey. I compared the square script transcription with the Japanese and English translations, and unmasked lost points in the translations. In reading the script, I also analyzed the old Mongolian text and highlighted some of the linguistic changes in the modern Mongolian language through the course of 700 years. As I did the transcription of the text, I captured the meaning of the whole text and filled the damaged portion with the 1962 transcription done by Dr. Osman Tuna and Dr. James Bosson. I realized later that there were other transcriptions done by different people including but not limited to Dr. Yo. Janchiv’s, Dr. D. Tumurtogoo’s, and Dr. Zuunast’s. In order to avoid possible mistakes in transcription on my part, I compared what I came up with theirs. My conclusion is that this document is a living proof of the colloquial Mongolian language and the closeness of the contemporary Buriat Mongolian dialect to the ancient Mongolian language during the Yuan period. Amongst the Mongolian scholars, this text can be categorized and be rediscovered as the newly known document in the Mongolian square script. This document will be of very high value as a research candidate for further studies in the area of Mongolian linguistics and a very good addition to the Mongolian square script collection.